Bedah Rumpon : The Cultural Tradition of Fishing in the Ajibarang Community of Banyumas - Muhammad Zainuddin; Muh. Sulaiman Dadiono; Wiwiet Teguh Taufani (Academic Letters, 2025)
The tradition of "bedah ​​rumpon" is a fishing technique passed down through generations by the people of Ajibarang, Banyumas. This paper aims to examine this practice ethnographically and ecologically as part of local wisdom in managing inland water resources. This paper demonstrates that bedah rumpon functions not only as a fishing technique but also has strong social and cultural dimensions, including elements of mutual cooperation, seasonal rituals, and local water conservation. Although its effectiveness has declined due to declining fish populations due to environmental degradation, this practice is still maintained as part of local identity.